2022
DOI: 10.3389/fgene.2022.1047231
|View full text |Cite
|
Sign up to set email alerts
|

A neutrophil extracellular traps-associated lncRNA signature predicts the clinical outcomes in patients with lung adenocarcinoma

Abstract: Backgrounds: Neutrophil extracellular traps (NETs) play an important role in the occurrence, metastasis, and immune escape of cancers. We aim to investigate Long non-coding RNAs (lncRNAs) that are correlated to NETs to find some potentially useful biomarkers for lung adenocarcinoma (LUAD), and to explore their correlations with immunotherapy and chemotherapy, as well as the tumor microenvironment.Methods: Based on the The Cancer Genome Atlas (TCGA) database, we identified the prognosis-related lncRNAs which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…We found that the anoikis-associated lncRNA AL365181.3 may be regulated by hsa-miR-31-5p to exert prooncogenic effects. In previous studies, AL365181.3 was identified as a neutrophil extracellular trap-associated lncRNA and has potential prognostic value for LUAD patients 51 . In addition, AL365181.3 has been identified as an iron death-associated lncRNA and has been verified to be significantly upregulated in a variety of NSCLC cell 52 .…”
Section: Discussionmentioning
confidence: 98%
“…We found that the anoikis-associated lncRNA AL365181.3 may be regulated by hsa-miR-31-5p to exert prooncogenic effects. In previous studies, AL365181.3 was identified as a neutrophil extracellular trap-associated lncRNA and has potential prognostic value for LUAD patients 51 . In addition, AL365181.3 has been identified as an iron death-associated lncRNA and has been verified to be significantly upregulated in a variety of NSCLC cell 52 .…”
Section: Discussionmentioning
confidence: 98%
“…Neutrophils are generated in great number in the bone marrow, as a crucial part of the bone marrow microenvironment, release NETs which may influence the bone marrow tumor immune microenvironment and, in turn, affect the prognosis of patients with myeloma. NETs have been implicated in a variety of cancerous disease (26)(27)(28)(29)(30)(31). However, the relationship between NETs and MM has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Its high expression indicates a worse prognosis and a more advanced stage in LUAD patients, and treatment targeted at relevant targets may inhibit further invasion of lung adenocarcinoma cells [33]. Some scholars have proposed that neutrophil extracellular traps (NETs) may play an important role in the occurrence and development of lung cancer, and AL365181.3 is involved in this process [34]. LINC01843 has also been used in some studies to predict the prognosis of lung adenocarcinoma [35].…”
Section: Discussionmentioning
confidence: 99%